Effect of complete feed or grazing and supplementation of lambs on performance,nutrient utilization and feed cost of production - CHATURVEDI, O H; KUMAR, SUSHIL; MISHRA, A K; ARORA, A L; KARIM, S A (The Indian Journal of Animal Sciences, 2011)
A study was conducted, to compare 2 feeding systems, viz. stall feeding (SF) and grazing plus supplementation (GR) evaluating body weight gain, nutrient utilization and feed cost of production of Avikalin lambs. SF animals received ad lib. complete feed (CF), GR animals were allowed grazing for 8 h and supplemented concentrate pellets @ 300 g/head/d. Intake in grazing animals was determined using chromium III oxide as internal marker. DM intake (g/ kgW0.75) by GR lambs was lower than SF lambs. Lower intake of DM by GR lambs was also reflected in lower DCP intake. The DM, DCP and ME intakes in terms of metabolic body weights by GR lambs were higher than their requirements, which further increased in SF lambs. Digestibility of DM, OM, CP, NDF, ADF, cellulose and hemicellulose was higher in GR animals. Average body weight gain and average daily gain in the SF group was higher than that of the GR group. Lower feed conversion ratio (8.7 v. 11.3 g/g) and higher feed cost of production (40.6 v. 28.2 Rs/kg live weight gain) were observed in SF animals than in GR animals. The SF system of feeding where CF was offered to lambs appeared superior in terms of intake and animal performance. Therefore the SF feeding system can be advocated as an alternative to grazing and supplementation feeding strategy for sheep production, especially where the pastures are highly eroded and need resting for regeneration or curing. Feeding of CF can also be adopted under adverse situations such as drought and famine, which are common phenomen in arid and semi-arid regions.